2016
DOI: 10.1021/acs.iecr.6b02064
|View full text |Cite
|
Sign up to set email alerts
|

Trace NaCl and Na2EDTA Mediated Synthesis of α-Calcium Sulfate Hemihydrate in Glycerol–Water Solution

Abstract: We report a new class of glycerol−water system to transform FGD gypsum into α-calcium sulfate hemihydrate (α-HH) mediated by trace NaCl and Na 2 EDTA to regulate the phase transformation rate as well as the crystal morphology to achieve crystals with high mechanical strength. NaCl plays a role in accelerating the nucleation and crystal growth process, whereas Na 2 EDTA regulates the morphology of α-HH from columnar to lamellar. The paste made from columnar α-HH with higher aspect ratio deserves higher dry bend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 31 publications
1
22
1
Order By: Relevance
“…For instance, a-HH particles with a low aspect ratio or spherical shape possess better injectability and mechanic strength, and are preferable for use as bone cements. 9,10 Therefore, in order to prepare a-HH products with low aspect ratios, crystal modiers, among which carboxylic acids are highly effective, 5,11,12 tend to be added during the transformation process. However, in alcohol water solutions, the inuence of crystal modiers on the morphology of a-HH crystals and transformation time from DH to a-HH has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a-HH particles with a low aspect ratio or spherical shape possess better injectability and mechanic strength, and are preferable for use as bone cements. 9,10 Therefore, in order to prepare a-HH products with low aspect ratios, crystal modiers, among which carboxylic acids are highly effective, 5,11,12 tend to be added during the transformation process. However, in alcohol water solutions, the inuence of crystal modiers on the morphology of a-HH crystals and transformation time from DH to a-HH has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Tan et al [22] found that long columnar crystals with uniform diameters could be obtained by adding acrylic acid (CH 2 =CH-COOH), which contained only one COOH and could not convert the α-CaSO 4 •0.5H 2 O from long columnar whiskers to short columnar crystals. However, the crystal habit of α-CaSO 4 •0.5H 2 O can be controlled by citric acid and ethylene diamine tetraacetic acid (EDTA) [28], which contain three and four COOH, respectively. Thus, it can be concluded that the crystal modifier must contain two or more COOH, and the separation between two COOH in the crystal modifier molecule cannot be more than two methylene/methine groups.…”
Section: Effect Of Amino Acid On the Crystal Habit Of α-Caso4• 05h2omentioning
confidence: 99%
“…3 In recent years, high-value utilization of I-PG has drawn signicant attention and so far, the most effective way to achieve high-value utilization of I-PG is to produce a-calcium sulphate hemihydrate (a-CaSO 4 $0.5H 2 O). [4][5][6] To date, methods for preparing a-CaSO 4 $0.5H 2 O crystals from CaSO 4 $2H 2 O mainly include autoclave hydrothermal, [7][8][9][10] atmospheric salt solution, [11][12][13][14] reverse microemulsion 15 and alcohol-water solution. [16][17][18] The autoclave hydrothermal method involves high temperature (usually above 120 C) and certain pressure, 19,20 which are not conducive to industrialization.…”
Section: Introductionmentioning
confidence: 99%